2022
DOI: 10.1002/jts.22873
|View full text |Cite
|
Sign up to set email alerts
|

Combining a stellate ganglion block with prolonged exposure therapy for posttraumatic stress disorder: A nonrandomized clinical trial

Abstract: Prolonged exposure therapy (PE) is an efficacious treatment for active duty service members and veterans with posttraumatic stress disorder (PTSD). However, PE is sometimes associated with high dropout rates, limited tolerability, and temporary symptom exacerbation during treatment. Stellate ganglion blocks (SGBs) are an emerging treatment that has the potential to enhance outcomes for PTSD when combined with trauma‐focused psychotherapy. To date, no study of which we are aware has examined the potential addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In keeping with our hypotheses and the study by Peterson and colleagues (Peterson et al, 2022), we did observe a statistically significant reduction in PTSD symptoms as measured by the CAPS-5 in mixed models (though not in paired t tests). There was a main effect of time, and after adjusting for multiple comparisons, there was a statistically significant decrease overall from baseline to 1 month, indicating that symptoms improved over the course of the study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In keeping with our hypotheses and the study by Peterson and colleagues (Peterson et al, 2022), we did observe a statistically significant reduction in PTSD symptoms as measured by the CAPS-5 in mixed models (though not in paired t tests). There was a main effect of time, and after adjusting for multiple comparisons, there was a statistically significant decrease overall from baseline to 1 month, indicating that symptoms improved over the course of the study.…”
Section: Discussionsupporting
confidence: 91%
“…It is also quite possible that delivering the full PE protocol (as in the Peterson et al study;Peterson et al, 2022) in combination with SGB is necessary to achieve greater symptom relief and functional PILOT STUDY OF STELLATE GANGLION BLOCK improvements. Indeed, several participants commented that they would have liked additional therapy sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, prior studies of civilians and veterans with PTSD showed that hyperarousal symptoms were associated with weaker neural habituation to aversive stimuli [ 59 ] and poorer response to Cognitive Processing Therapy [ 60 ]. As one pilot study combining SGB with Prolonged Exposure to treat combat-related PTSD ( N = 12) reported clinically significant change without evidence of more adverse events compared to standalone SGB and PE trials [ 61 ], additional studies comparing the effects of SGB delivered alone or delivered alongside TFTs are warranted. Indeed, two clinical trials pairing SGB and TFT are ongoing and will hopefully inform how to best combine or sequence these approaches in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 12 years, stellate ganglion block has been used successfully to treat thousands of patients with significant symptoms of posttraumatic stress disorder. There have been over 18 original studies published in the peer-reviewed literature which support the use of SGB for this indication [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%